2018
DOI: 10.1016/j.niox.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Lowering of blood pressure after nitrate-rich vegetable consumption is abolished with the co-ingestion of thiocyanate-rich vegetables in healthy normotensive males

Abstract: A diet rich in vegetables is known to provide cardioprotection. However, it is unclear how the consumption of different vegetables might interact to influence vascular health. This study tested the hypothesis that nitrate-rich vegetable consumption would lower systolic blood pressure but that this effect would be abolished when nitrate-rich and thiocyanate-rich vegetables are co-ingested. On four separate occasions, and in a randomized cross-over design, eleven healthy males reported to the laboratory and cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 54 publications
1
18
0
Order By: Relevance
“…These findings indicate that other dietary components may be responsible for dampening the beneficial effects of dietary nitrate. This notion was recently supported by findings from Dewhurst-Trigg et al ( 44 ) that in high to moderate nitrate containing vegetables including cabbage and broccoli, the cardiovascular benefits of nitrate were completely blocked in the co-presence of thiocyanate, which is thought to block the enterosalivary metabolism of dietary nitrate to NO via the nitrate–nitrite–NO pathway. Thus, it is possible such mechanisms are at play in our cohort.…”
Section: Discussionmentioning
confidence: 73%
“…These findings indicate that other dietary components may be responsible for dampening the beneficial effects of dietary nitrate. This notion was recently supported by findings from Dewhurst-Trigg et al ( 44 ) that in high to moderate nitrate containing vegetables including cabbage and broccoli, the cardiovascular benefits of nitrate were completely blocked in the co-presence of thiocyanate, which is thought to block the enterosalivary metabolism of dietary nitrate to NO via the nitrate–nitrite–NO pathway. Thus, it is possible such mechanisms are at play in our cohort.…”
Section: Discussionmentioning
confidence: 73%
“…Alternatively, there is compelling evidence to suggest that consumption of other dietary compounds alongside NO 3 − may have the capacity to influence response to this compound, such that an individual’s background diet could determine (at least transiently) their status as a NO 3 − ‘responder’ or ‘non-responder’. For example, consumption of glucosinolate-rich vegetables, such as those from the Brassica family like broccoli, cauliflower, and cabbage, proximal to consumption of NO 3 − -rich vegetables was shown to blunt the BP lowering response of the latter [ 130 ]. Interestingly, this appears to be related to a similar mechanism to which smoking attenuates the effect of NO 3 − .…”
Section: Main Textmentioning
confidence: 99%
“…Specifically, during processes that result in plant cell membrane damage such as mastication, glucosinolates are exposed to the enzyme myrosinase, which catalyses the hydrolysis of glucosinolates into thiocyanate [ 161 ]. Although consumption of thiocyanate-rich vegetables leads to lower salivary and plasma thiocyanate concentrations compared with smoking, Dewhurst-Trigg et al [ 130 ] showed that the BP-lowering effect of a NO 3 − -rich smoothie was attenuated by the presence of thiocyanate rich vegetables. In that study, thiocyanate did not seem to interfere with NO 3 − transport into the mouth (as evident by similar salivary NO 3 − concentrations when NO 3 − was consumed alongside vegetables that were both high and low in thiocyanate), suggesting that thiocyanate may influence other aspects of NO 3 − metabolism.…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, previous studies have indicated that the wider dietary context can modulate the effects of inorganic nitrate on BP. For example, 1 study found that the antihypertensive effects of nitrate were abolished when this compound was consumed alongside thiocyanate-rich vegetables such as broccoli ( 24 ), whereas another suggested potential BP-increasing effects of nitrate when consumed alongside dietary sulfate ( 25 ).…”
Section: Discussionmentioning
confidence: 99%